KARAKTERISASI SENYAWA ASAM LEMAK PADA AKAR TUMBUHAN LANGSAT (Lansium domesticum Correa) (CHARACTERIZATION OF FATTY ACID COMPOUNDS IN THE ROOT OF LANGSAT PLANT (Lansium domesticum Correa) - Azzizah Laila; Harlia Harlia; Rudyansyah Rudyansyah (Indonesian Journal of Pure and Applied Chemistry, 2022)
The chemical structure of fatty acid compounds in plant parts other than seeds and fruit is still not widely known even though it has various benefits. One of the plants known to contain fatty acid compounds is Langsat. This research was conducted to characterize the structure of fatty acid compounds and the content of secondary metabolites in the roots of the langsat plant. The fatty acid characterization process was carried out by spectroscopy while the secondary metabolite content was analyzed by phytochemical screening test. Based on the spectrum of Proton Nuclear Magnetic Resonance (H-NMR) in acetone-d6 solvent at a frequency of 500 MHz, chemical shift data were obtained at 0.89 ppm (t, 3H), 1.33 ppm (m, 6H), 1.63 ppm (m, 2H), 2.33 ppm (t, 2H) and 8.14 ppm (s, 1H) and the results of phytochemical tests on the methanol extract of langsat root are known to contain alkaloids, terpenoids, flavonoids, phenolics, and saponins. Based on these data and compared with the literature, it is suspected that L1 isolates have similarities with the structure of compounds belonging to the fatty acid group.